Influence of Clay Particles on the Transport and Retention of Titanium Dioxide Nanoparticles in Quartz Sand - Cai, Li; Meiping Tong; Wang, Xueting; Kim, Hyunjung (Environmental Science & Technology, 2014)
This study investigated the influence of two representative suspended clay particles, bentonite and kaolinite, on the transport of titanium dioxide nanoparticles (nTiO2) in saturated quartz sand in both NaCl (1 and 10 mM ionic strength) and CaCl2 solutions (0.1 and 1 mM ionic strength) at pH 7. The breakthrough curves of nTiO2 with bentonite or kaolinite were higher than those without the presence of clay particles in NaCl solutions, indicating that both types of clay particles increased nTiO2 transport in NaCl solutions. Moreover, the enhancement of nTiO2 transport was more significant when bentonite was present in nTiO2 suspensions relative to kaolinite. Similar to NaCl solutions, in CaCl2 solutions, the breakthrough curves of nTiO2 with bentonite were also higher than those without clay particles, while the breakthrough curves of nTiO2 with kaolinite were lower than those without clay particles. Clearly, in CaCl2 solutions, the presence of bentonite in suspensions increased nTiO2 transport, whereas, kaolinite decreased nTiO2 transport in quartz sand. The attachment of nTiO2 onto clay particles (both bentonite and kaolinite) were observed under all experimental conditions. The increased transport of nTiO2 in most experimental conditions (except for kaolinite in CaCl2 solutions) was attributed mainly to the clay-facilitated nTiO2 transport. The straining of larger nTiO2-kaolinite clusters yet contributed to the decreased transport (enhanced retention) of nTiO2 in divalent CaCl2 solutions when kaolinite particles were copresent in suspensions.